Quo Vadis: Legal certainty of environmental protection in investment activities post job creation law - Anwar, Mashuril; Fathonah, Rini (International Journal on Social Science, Economics and Art, 2024)
Legal certainty in environmental protection is one of the issues of investing in Indonesia. After the issuance of the Job Creation Law, an existential question that emerged was how the investment regime of the Job Creation Law supports legal certainty for environmental protection. In this situation, there is a possibility of ignoring the legal certainty of environmental protection when making investments. However, legal certainty is highly expected by investors to ensure that investments made do not contradict environmental sustainability. Therefore, this research aims to analyze the role of investment in environmental protection, as well as analyze the legal certainty of environmental protection in the investment regime of the Job Creation Law. This research is normative or doctrinal research, where the object of research is legislation in the investment sector, supported by the results of a literature study. Apart from that, this research uses a qualitative analysis method by describing the data obtained based on the problem. The results of this research show that investment activities will always be in contact with environmental sustainability. However, the issuance of the Job Creation Law simplifies and facilitates investment activities but provides legal certainty in environmental protection